Association of Growth Velocity with Insulin-Like Growth Factor-1 and Insulin-Like Growth Factor Binding Protein-3 Levels in Children with a Vegan Diet - Arie Purwana; Budiono Budiono; Jose RL Batubara; Muhammad Faizi (Journal of Biomedicine and Translational Research, 2020)
Background: The vegan diet in children provides the benefit of reducing the risk of being overweight and improving the fat profile. The risk that can occur in the provision of a vegan diet in children is anthropometric size below reference and low caloric intake. Growth hormone (GH) and Insulin like Growth Factors (IGFs) are powerful stimulators for longitudinal growth of bone and require insulin-like growth factor binding protein (IGFBPs) which acts as a transport protein for IGF-1. A vegan diet with lower calorie intake in children has lower IGF-I levels than children with an omnivorous diet.